Strength and fluoride release characteristics of a calcium fluoride based dental nanocomposite - Xu, Hockin H.K.; Moreau, Jennifer L.; Sun, Limin; Chow, Laurence C. (Biomaterials, 2008)
Secondary caries and restoration fracture remain the two most common problems in restorative dentistry. Release of fluoride ions (F) could be a substantial benefit because F could enrich neighboring enamel or dentin to combat caries. The objective of this study was to incorporate novel CaF 2 nanoparticles into dental resin to develop stress-bearing, F-releasing nanocomposite. CaF 2 nanoparticles, prepared in our laboratories for the first time, were combined with reinforcing whisker fillers in a resin. Flexural strength (mean ± sd; n = 6) was 110 ± 11 MPa for the composite containing 30% CaF 2 and 35% whiskers by mass. It matched the 108 ± 19 MPa of a stress-bearing, non-releasing commercial composite (Tukey's at 0.05). The composite containing 20% CaF 2 had a cumulative F release of 2.34 ± 0.26 mmol/L at 10 weeks. The initial F release rate was 2 μg/(h cm 2), and the sustained release rate after 10 weeks was 0.29 μg/(h cm 2). These values exceeded the reported releases of traditional and resin-modified glass ionomer materials. In summary, nanocomposites were developed with relatively high strength as well as sustained release of fluoride ions, a combination not available in current materials. These strong and F-releasing composites may yield restorations that can reduce the occurrence of both secondary caries and restoration fracture.